Energy efficient technology adoption and low-income households in the EU: What is the evidence? - Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
This paper studies the adoption of high-cost, medium-cost, and low-cost energy-efficient technologies (EETs) by income categories in eight European Union countries, relying on demographically representative household surveys carried out simultaneously among about 15,000 households in France, Germany, Italy, Poland, Romania, Spain, Sweden, and the United Kingdom. The statistical-econ-ometric analyses allow the effects of income to differ by income quartiles in each country. For retrofit measures, the findings suggest that homeowners falling into the lowest income quartile exhibit lower adoption propensities than those falling into the highest income quartile. These findings provide support for policies tar-geting "poor homeowners", particularly in lower-income countries with a high share of owner-occupiers such as Poland and Romania. Further, differences in adoption propensities across income quartiles also exist for medium- and low-cost EETs such as appliances and light bulbs. Finally, analyzing factors related to homeowners' receiving financial support for retrofit measures from govern-ments or utilities suggests that differences in implementation rates between the highest and lowest income quartile would likely have been higher without such support schemes in place. For the United Kingdom (but not for other countries) these schemes appeared to have had a progressive effect.
urn:nbn:de:0011-n-497244-18
Keywords: 330; energy poverty; energy efficiency; adoption; poor homeowners; subsidies; econometrics